PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KREATIVITAS BELAJAR BIOLOGI SISWA DI SMA NEGERI 1 BARUMUN - Zulhandri Zulhandri; Sahlan Tuah; Yusni Atifah (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The problem in this study is the creation of learning the biology of students is still low in class XI IPA 2 SMA Negeri 1 Barumun, less varied learning models. The purpose of this research is to know the enhancement of student biology learning creativity through problem-based learning on tissue material on plants in class XI IPA 2 at SMA Negeri 1 Barumun year 2018-2019 lesson, through learning-based problems, the research approach used in this research is class action research. This research located at SMA Negeri 1 Barumun with the address of the cross-Riau road implemented after the approval letter of this research was issued. The subject is the class XI IPA 2 SMA Negeri 1 Barumun While the object is a test of learning creativity of students by using a problem-based learning model on tissue material in plants in class XI IPA 2 SMA Negeri 1 Barumun. The results of the creativity test on the I cycle gained an average of 72.25 with a percentage of 56.25% increase in cycle II by an average of 81.93 with compensation of 71.25%. Keywords: Creativity, learning outcomes, problem-based learning Model.